BIMBINGAN KONSELING ISLAMI UNTUK MENANGGULANGI KECANDUAN TIK TOK ANAK USIA DINI DI TKIT HAQQUL YAQIN KARANG BEJELO, GONJAK, KEC. PRAYA, KAB. LOMBOK TENGAH - Sukardiman, Sukardiman (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2023)
Islamic counseling is one of the fundamental counseling to shape human character for the better, in the sense of humanizing other human beings to get out of the problems they face, especially moral problems which are experiencing a decline in the current global era with extraordinary flows of technology and information, such as One application that is developing very rapidly, namely Tik Tok. Tik Tok is an application that has become a new trend in the world, especially in Indonesia, this application has even become a popular culture in our society, which is horrendous, liked and followed. however, even though this application is popular there will always be negative consequences, especially for early childhood TK IT Haqqul Yaqin Kindergarten, this is the main focus of solving problems from this school through Islamic counseling which is carried out continuously. Researchers in looking at the problem of addiction to Tik Tok IT Haqqul Yaqin Kindergarten students used a type of qualitative research, namely through observation, interviews and documentation. The results of the study show the strategy of the teacher (counselor) in dealing with children addicted to Tik Tok, namely (1) habituation, such as saying greetings when they arrive at school, memorizing short verses, daily prayers, pillars of faith and Islam. (2) giving examples by the teacher, (3) providing education to parents of students.Keywords: Islamic Counseling, Tik Tok, and Early Childhood